Fractal and wavelet image compression techniques - Welstead Stephen (Washington SPIE, 1999)
Interest in image compression for Internet and other multimedia applications has spurred research into compression techniques that will increase storage capabilities and transmission speed. This tutorial provides a practical guide to fractal and wavelet
Keywords: Fractals; Image compression-mathematics; Image processing-digital techniques; Wavelets(Mathematics)